Results of combined antiangiogenic activity on corneal neovascularization. Experimental and morphological study - V. R. Mamikpnyan; T. M. Voevodina; A. A. Fyodorov; M. V. Budzinskaya; M. L. Balayan (Biomedical Photonics, 2014)
Results of comparative experimental and morphological study of activity on corneal neovascularization in rabbit’s eye of photodynamic therapy with Photosense and antiangiogenic therapy with Avastin (bevacizumab) alone, and in its combination are represented. The treatment was performed in regimens: 1) photodynamic therapy with Photosense (single intravenous injection in dose of 0.3 mg/kg 72 h prior to laser irradiation, power density of irradiation 500 mW/cm2, wavelength 675 nm); 2) drug antiangiogenic therapy with Avastin (single subconjuctival introduction at dose of 1.25 mg); 3) photodynamic therapy with Photosense (in described regimen) in combination with subconjuctival introduction of Avastin at dose of 1.25 mg immediately prior to irradiation. Combined photodynamic therapy with antiangiogenic therapy allows to obtain almost complete occlusion in all regions of corneal neovascular bed with shorter time interval comparing with those for monoregimens. In case of blood flow retention in great vessels courses of combined modality treatment may be repeated. The absence of side-effects on surrounding tissues and the recovery of optical characteristics of cornea may allow to use this upcoming method in clinical practice.